Peran Mahasiswa Ilmu Komputer dalam Mendorong Inovasi Pelayanan Publik Berbasis Digital: Studi Literatur Sistematis dan Eksplorasi Kontekstual di Purwokerto - Ikhwan Nurdin; Anggit Apriadi Putra; Krisna Ardiva Sandra; Mirzozoda Mirzoahmad (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Digital transformation in public services has become a strategic agenda in realizing effective, transparent, and responsive governance. Amidst the wave of digitalization, computer science students occupy an important position as agents of innovation who are capable of integrating technological solutions into the delivery of public services. This study aims to systematically examine the contribution of Computer Science students in promoting digital-based public service innovation in the Purwokerto region. The research approach uses the Systematic Literature Review (SLR) method, supplemented by contextual exploration through primary data in the form of interviews and participatory observation. The study found five main roles of students, namely: (1) developers of public service applications based on local needs; (2) facilitators of digital literacy for government officials and the community; (3) agents of change in the culture of digital bureaucracy; (4) collaborative partners in the formulation of technology policies; and (5) pioneers of digital ethics and data security. These findings indicate that the active involvement of students in a multidisciplinary manner is a crucial factor in the success of digital public service transformation, especially in regional contexts such as Purwokerto. This study recommends the integration of a public service project-based curriculum, strengthening the synergy between the government and universities, and inclusive policies that support student involvement in regional digital service innovation.